2022
DOI: 10.1111/nyas.14789
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of choir singing on complex auditory encoding in the aging brain: An ERP study

Abstract: Aging is accompanied by difficulties in auditory information processing, especially in more complex sound environments. Choir singing requires efficient processing of multiple sound features and could, therefore, mitigate the detrimental effects of aging on complex auditory encoding. We recorded auditory event-related potentials during passive listening of sounds in healthy older adult (≥ 60 years) choir singers and nonsinger controls. We conducted a complex oddball condition involving encoding of abstract reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
5
0
1
Order By: Relevance
“…In this study, our aim was to determine whether regular choir singing can have long-term benefits on cognitive, emotional, and social functioning in healthy older adults. Previous studies in older adults have identified benefits of group singing on various aspects of wellbeing, including cognition, physical health, mood, social wellbeing, and QOL ( Johnson et al, 2013 , 2020 ; Coulton et al, 2015 ; Fu et al, 2018 ; Pentikäinen et al, 2021 , 2022 ). Critically, however, evidence from longer-term follow-up periods is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our aim was to determine whether regular choir singing can have long-term benefits on cognitive, emotional, and social functioning in healthy older adults. Previous studies in older adults have identified benefits of group singing on various aspects of wellbeing, including cognition, physical health, mood, social wellbeing, and QOL ( Johnson et al, 2013 , 2020 ; Coulton et al, 2015 ; Fu et al, 2018 ; Pentikäinen et al, 2021 , 2022 ). Critically, however, evidence from longer-term follow-up periods is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…One study was able to show that playing the cello makes use of some of the same neuronal networks as singing, such as Heschl’s gyrus, anterior insula, and anterior cingulate cortex ( Segado et al, 2018 ). In an auditory event-related potentials (ERP) study, healthy choir singers and nonsinger controls aged over 60 years were investigated when listening passively to sounds ( Pentikäinen et al, 2022 ). The authors used two simple oddball conditions, in which the pitch or spatial location of the sounds was varied, and a complex oddball condition involving encoding of abstract regularities in combinations of both pitch and location features.…”
Section: Neural Mechanisms Of Choral Singingmentioning
confidence: 99%
“…As the N1 ERP component reflects automatic stimulus processing and MMN is an indicator of stimulus change or of a neural-mismatch process triggered by a rare deviant stimulus at the presence of a neural trace of the frequent standard stimulus ( cf. Mueller et al, 2008 ), the authors concluded that regular choir singing is associated with both more effective adaptation to simple sound features and more enhanced encoding of complex auditory regularities ( Pentikäinen et al, 2022 ). A study that may provide insight into the special case of choral singing investigated the role of laypeople’s ability to sing and to move to the beat of a rhythmic stimulus ( Dalla Bella et al, 2015 ).…”
Section: Neural Mechanisms Of Choral Singingmentioning
confidence: 99%
“…Furthermore, MIT, a singing-based intervention for treating nonfluent aphasia, has been shown to improve connected speech, naming, and repetition ( Sparks et al, 1974 ; Van Der Meulen et al, 2014 ; Zumbansen et al, 2014 ) and linking the positive effects to temporal and frontal speech motor areas, either in the left ( Belin et al, 1996 ; Breier et al, 2011 ) or right ( Schlaug et al, 2008 ; Wan et al, 2014 ; Tabei et al, 2016 ) hemisphere. In the healthy older adults, regular singing has recently been linked to enhanced executive function ( Pentikäinen et al, 2021 ; Vetere et al, 2024 ), frontotemporal auditory functioning ( Pentikäinen et al, 2022 ), structural connectivity ( Perron et al, 2021 ), and structural plasticity in auditory and dorsal speech regions ( Perron et al, 2022 ), suggesting that it may have neuroprotective effects in aging.…”
Section: Introductionmentioning
confidence: 99%